2011
DOI: 10.2478/v10078-011-0054-5
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure Combining Strength and Aerobic Training

Abstract: The combination of Strength Training (ST) with Aerobic Training (AT) exercises in the same training session, which commonly appears in literature as the concurrent training, is widely used in fitness and physical condition programs, especially when the aim is to increase the energy expenditure during and after training session. The aim of this study was to identify, through literature, whether the combination of exercises of the ST with exercises of the AT allows changes in body composition and energy expendit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…Both of these studies involved concurrent training programs and recorded an increase in metabolic expenditure following the programs. This increase, however, was smaller, rising by a mean of 1200 MET-mins/week 73,74 , than that of our study in which a mean increase of 3200 MET-mins/week was recorded (Table 5). In our study, the AT group had a higher metabolic expenditure than the ST group and the CG, results that are in line with research by Bakker et al (2017), Scharhag-Rosenberger (2017), Ramírez-Vélez (2017) and Ostendorf (2019) in which it was detected that in AT programs, metabolic expenditure is higher than when ST or mixed training is implemented, especially in moderate physical activity [75][76][77][78][79][80] .…”
Section: Discussioncontrasting
confidence: 82%
“…Both of these studies involved concurrent training programs and recorded an increase in metabolic expenditure following the programs. This increase, however, was smaller, rising by a mean of 1200 MET-mins/week 73,74 , than that of our study in which a mean increase of 3200 MET-mins/week was recorded (Table 5). In our study, the AT group had a higher metabolic expenditure than the ST group and the CG, results that are in line with research by Bakker et al (2017), Scharhag-Rosenberger (2017), Ramírez-Vélez (2017) and Ostendorf (2019) in which it was detected that in AT programs, metabolic expenditure is higher than when ST or mixed training is implemented, especially in moderate physical activity [75][76][77][78][79][80] .…”
Section: Discussioncontrasting
confidence: 82%
“…For, example, Di Blasio et al [10] showed that the post-exercise (recovery) energy expenditure (oxygen consumption) is significantly greater after the integrated than after the serial combined protocol. On the other hand, simply changing the order of endurance and strength exercises (2 forms of serial combined training) does not seem to affect the energy expenditure during [39,40] or after exercise [10]. There are, however, studies which demonstrate that the order of endurance and strength exercise may affect the post-exercise energy expenditure [39,40].…”
Section: Physical Fitness and Functional Capacitymentioning
confidence: 99%
“…Thus, a strategy that may be used is concurrent training (Coffey and Hawley, 2017). Furthermore, Vilaça et al (2011) emphasized that a combination of AE and RE (regardless of order) is beneficial for reducing BF and increasing energy expenditure during and after PE sessions.…”
Section: Introductionmentioning
confidence: 99%